التلوث البيئي في ماليزيا: دراسة تحليلية لوسائل الوقاية وطرق العلاج في ضوء السنة النبوية - Mardhiahtul Adawiyah binti Md Yunus (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
This study aims to find out the causes of haze, acid rain and solid waste as well as the developments of these pollutions. To complement the research, certain appropriate hadiths have been included as to figure out ways to solve the problem. The inclusion of hadiths also act as solid reminders to muslims as to inculcate Rasulullah's teachings in the preservation of the environment. The research uses several methodologies, for instance, the inductive method which is to read thoroughly of the information about haze,acid rain and solid waste in Malaysia from statistics and newspapers. While the other methodology used is the analysis methode, which is to analyse the reasonable hadiths of preservation and conservation of the environment,by extracting the benefits and useful teachings of the hadiths. Most importantly, the research will be able to determine the causes of the pollutions and its development, as well as the effects of the pollution on earth and its inhabitants. This research will hopefully provide necessary information to the people that hadiths provide guidance in resolving the effects of pollutions.